Peran Mahkamah Konstitusi Sebagai Pelaku Sistem Kekuasaan Kehakiman di Indonesia - Suci Wulandari; Pingkan Utari; Fergio Rizkya Refin; Moh. Bagus; Akhmad Fandik; Thobary, Amim (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2023)
The Constitutional Court is one of the highest state institutions in Indonesia as an actor in the judiciary along with the Supreme Court. The Constitutional Court has the authority to examine, examine, and decide on laws deemed to be contrary to the 1945 Constitution of the Republic of Indonesia. Therefore, decisions from the Constitutional Court are final and binding in that there are no other legal remedies. In order to review the law against the 1945 Constitution of the Republic of Indonesia, both formal and material tests can be carried out. Based on this, this research will provide a new reflection on how the Constitutional Court enforces the law and provides constitutional protection to every citizen in accordance with the legal basis in Indonesia. This study uses a normative juridical approach and materials taken through literature studies. The aim of this research is to find out about the Constitutional Court and the Judicial Power System in Indonesia. Through descriptive analysis, the author then collects reading sources through relevant laws, books and journals. Then, the literature material is processed using an inductive method where the researcher examines and draws conclusions from a case. From the results of this research, it turns out that the Constitutional Court is not only an actor of judicial power but also a protector of citizens' constitutional rights so that they are not violated.